Pengelolaan Taman Mumbul Sebagai Daya Tarik Wisata Spiritual Di Desa Sangeh, Kecamatan Abiansemal, Kabupaten Badung - Wulandari, Aissyah; Adikampana, I Made (JURNAL DESTINASI PARIWISATA; Vol 5 No 2 (2017): VOL 5, NO 2 (2017): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2018)
Visiting an alternative tourism that adopt sustainable tourism development concept is being trend for tourist. Bali as the best tourism destination in the world uses this chance with developing spiritual tourism that known with Tri Hita Karana and one of them is Taman Mumbul that located in Desa Sangeh, Kecamatan Abiansemal, Kabupaten Badung. This tourist attraction is offering the spiritual attractions named by melukat. But there’s many constraints that need further handling by the management in order to make a positive impression from the tourist perception. The purpose of this research is for knowing about tourist perception and describing how the ideal management that can implemented in Taman Mumbul. The data that used in this research is quantitative and qualitative approach by observation, documentation, literature, interview and questionnaire. For data analysis, it used explorative descriptive and Likert Scale with component of tourist destination theory and sustainable tourism concept. The result from this research indicates that tourist perception for Taman Mumbul management get a good judgement although three aspects in facility variable obtain a bad judgement. Then, it formulated into the ideal management form that contained about protection of security and comfort, community empowerment and preservation of natural and culture environment. In clonclusion, the management have done a good performance but it will be better if they alleviate the constraints that they have faced in order to create tourist satisfaction when they come to Taman Mumbul.   Keywords : management, spiritual tourism, tourist attraction, tourist perception.